Integrating Collaborative Reasoning and Strategy Instruction to Improve Second Graders' Opinion Writing - Traga Philippakos, Zoi A.; MacArthur, Charles A. (Reading & writing quarterly, 2020)
The purpose of this study was to examine the effects of an approach to teaching opinion writing in the primary grades that combined collaborative reasoning with strategy instruction. Four teachers and 80 students were randomly assigned to treatment and control conditions for 10 days of instruction in opinion writing. Students wrote opinion essays at pretest and posttest, participated in interviews, and completed a self-efficacy questionnaire. Teachers completed an efficacy questionnaire and participated in interviews. Analysis found a statistically significant effect of treatment on overall quality of essays. Analysis of elements found that both groups included more reasons and evidence at posttest, but students in the treatment condition included more elements in the introduction and conclusion. No statistically significant differences were found for student or teacher efficacy.